2011
DOI: 10.1111/j.1742-4658.2011.08389.x
|View full text |Cite
|
Sign up to set email alerts
|

Stimulatory effect of α‐synuclein on the tau‐phosphorylation by GSK‐3β

Abstract: Hyperphosphorylation of tau protein (tau) causes neurodegenerative diseases such as Alzheimer's disease (AD). Recent studies of the physiological correlation between tau and a-synuclein (a-SN) have demonstrated that: (a) phosphorylated tau is also present in Lewy bodies, which are cytoplasmic inclusions formed by abnormal aggregation of a-SN; and (b) the neurotoxin 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) increases the phosphorylation of tau as well as the protein level of a-SN in cultured neuronal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(78 citation statements)
references
References 28 publications
(43 reference statements)
4
74
0
Order By: Relevance
“…25,26 The aforementioned studies combined with our current results suggest that hyperactivation of GSK-3β may be the primary mechanism by which this protein is linked to PD (Figure 7). Indeed, a growing body of evidence from our laboratory and others define the important roles, kinases, such as GSK-3β, CK2, PLK2 and 3, and GRK1-5 have in the development and pathology of PD through the phosphorylation of α-Syn and Tau 16,[18][19][20][21][22][23][24][53][54][55][56][57] (Supplementary Table S3 and associated references).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25,26 The aforementioned studies combined with our current results suggest that hyperactivation of GSK-3β may be the primary mechanism by which this protein is linked to PD (Figure 7). Indeed, a growing body of evidence from our laboratory and others define the important roles, kinases, such as GSK-3β, CK2, PLK2 and 3, and GRK1-5 have in the development and pathology of PD through the phosphorylation of α-Syn and Tau 16,[18][19][20][21][22][23][24][53][54][55][56][57] (Supplementary Table S3 and associated references).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study also showed that in in vitro kinase reactions, GSK3-β-mediated phosphorylation of Tau was increased in the presence of α-Syn in a dose-dependent manner. 57 These cumulative findings demonstrate that both α-Syn and Tau can modulate the toxic production of their phospho-proteins, in a manner that is subtly nuanced (Figure 7). Future experiments will delineate the exact signaling pathways altered by GSK-3β in the hGSK3-β-S9A mouse model, and as such, may provide a more thorough view as to whether phosphorylation of α-Syn occurs directly or indirectly via p-GSK3-β-Y216 and why the occurrence of accumulated p-α-Syn and p-Tau are restricted to the SN.…”
Section: 62mentioning
confidence: 99%
“…Recent postmortem studies showed increased accumulation of p-tau in the striata of PD patients and in the A53T mutant mouse model [343,577], related to increased activity of GSK-3β [566,579]. This is stimulated by AS that associates with the actin cytoskeleton [585] and by GSK-3β [568]. DA D1 receptor activation induces tau phosphorylation via cyclin-dependent kinase 5 (cdk5) and GSK-3β signalling pathways [586].…”
Section: α-Synuclein and Protein Interactionsmentioning
confidence: 99%
“…Accumulated α-syn (promoted by oxidative stress) has a stimulatory effect on tau phosphorylation by glycogen synthase kinase-3β (GSK-3β), a major kinase that hyperphosphorylates tau to produce pathologic forms [ 242 ], while the chaperone HSP70 may suppress α-syn-mediated tau phosphorylation in initial disease stages [ 243 ]. In MPTP models, α-syn has been shown to induce GSK-3β-catalyzed tau phosphorylation [ 244 , 245 ].…”
Section: Interaction Between α-Syn and Other Proteinsmentioning
confidence: 99%